Ready to Wear Deluxe Bergaya Holo-Cottagecore Inspirasi Troides Helena dengan Teknik Embellishment dan Painting - Putri Nurrahayu, Meida; Albani, Haidarsyah Dwi; Fitra, Anissa (Jurusan Seni Rupa ISBI Bandung, 2024)
The creation of ready to wear deluxe inspired by Troides helena butterflies has made a major contribution to the development of fashion innovation. The beautiful shape of the wings and their rarity encourage craftsmen to create creative products. The creation of this work combines technological developments in the form of Holograms and Cottagecore style. The use of this style is considered to be able to provide suitability to the concept with a rustic, natural and modern theme which is adapted to the Trend Forecast, Co-Exist: 2023-2024. The work approach also plays with various elements such as color, shape, pattern and motif from the use of embellishment techniques and painting techniques. From several collections of ideas, concepts and processes, the work is realized through a creation method which contains three stages, namely exploration, design and realization. A total of two (2) looks were presented in the creation of this work.